Research on adaptability in horizontal curve negotiation of HTS maglev train - LI Qiang; HE Peiheng; ZHENG Jie; DENG Bin; DENG Zigang (机车电传动)
To enhance the curve negotiation performance of high-temperature superconducting (HTS) maglev trains equipped with a rigid levitation frame, this paper proposes a semi-decoupled levitation frame structure with specific degrees of freedom in both pitching and yawing. Initially, a dynamic theoretical model for HTS maglev trains was established, utilizing linear characteristics derived by simplifying the levitation and guidance forces stemming from HTS. This theoretical model was confirmed rational following the validation through dynamic response simulations conducted using UM software under periodic excitations. Subsequently, UM software was further utilized to assess the horizontal curve-passing performance of HTS maglev trains. Furthermore, comparisons were made regarding the impacts of different vertical and lateral torsional rigidities of levitation frames, along with varying air spring vertical rigidities on Dewar lateral and vertical displacements. The simulation results indicate improved adaptability in the proposed semi-decoupled levitation frame with specific pitching and rolling degrees of freedom on curved and twisted track configurations. By reducing the adverse effects of the framework on the levitation system and maximizing the pinning effect characteristics of HTS, this approach demonstrates effective in enhancing the trains' curve-passing performance. Additionally, an appropriate air spring rigidity is also found a contributor to effectively suppressing Dewar vibration, thus further ensuring the operational quality of trains. This paper conclusively proposes a levitation system solution that aligns with the safety requirements of train operation, displaying a strong potential to improve the curve-passing performance of HTS trains.